Ziran : the philosophy of spontaneous self-causation - Bruya, Brian, 1966- (Albany : SUNY Press, 2022)
"Ziran, an idea from ancient Daoism, defies easy translation into English but can almost be captured by the term "spontaneity." It means "self-causation," if "self" is understood as fundamentally plural, and "causation" is understood as sensitivity and responsiveness. Applying ziran to the fields of action theory, attention theory, and aesthetics, Brian Bruya uses easy-to-read, straightforward prose to show, step-by-step, how this philosophical concept from an ancient tradition can be used to advance theory today. Incorporated into contemporary philosophy of action, ziran opens us to the notion of movement and action as self-organizing. Incorporated into contemporary cognitive science, ziran opens us to the possibility of effortless attention, contrary to the reigning paradigm. Incorporated into contemporary aesthetics, ziran opens us to a new category of art--somatic art--and a new, refined understanding of improvisation"--
Ziran and its absence in western philosophy -- Saving natural human action from the paradox of spontaneity -- Effortless attention : a missing concept in contemporary cognitive science -- Broadening aesthetics : spontaneity, the somatic arts, and improvisation.
Includes bibliographical references (pages 141-143) and index.
Print version record.
JSTOR
Keywords: Spontaneity (Philosophy); Taoist philosophy; Spontanéité (Philosophie); Philosophie taoïste.; PHILOSOPHY / Taoist; Spontaneity (Philosophy); Taoist philosophy